Langevin transducer with a stepped polymer horn. (11th August 2021) - Wu, Zihao; He, Xiping; Zheng, Huan; Zhu, Xingmin; Liu, Qiang
Abstract: Here, polyphenylene sulfide (PPS) with high Young's modulus and low loss was used as the front head material of a Langevin transducer for high-frequency vibration of mechanical antennas. In this study, transducer 1# with the front head and rear end made of PPS and steel, respectively, and transducer 2# with both the front head and rear end made of PPS, are designed and fabricated. Tests demonstrate that when the transducer's size is fixed and the front head is made of PPS, a greater vibration amplitude of the front head surface and the amplitude-to-voltage ratio can be obtained when the rear end is made of steel. The highest temperature of the two transducers is located at the highest strain area, consistent with the theoretical calculation. Besides, the PPS-based transducer's bandwidth is relatively large, conducive to the transmission of more signals.